Rekomendasi Pengembangan Program Tanggung Jawab Sosial dan Lingkungan/Corporate Social Responsibility (CSR) Bidang Lingkungan PT. Apac Inti Corpora (Terkait Sumber Daya Air di Kelurahan Harjosari, Kecamatan Bawen, Kabupaten Semarang) - Florentina Mediana Dessy B Soewardjo; Azis Nur Bambang; Suherman S (Ekosains, 2016)
PT Apac Inti Corpora (AIC), a textile industry in Semarang Regency implements several kinds of CSR programmes, such as education support, health check up,  and clean water supply to fulfill  community needs on water, in  Harjosari Village, Bawen District, Semarang Regency.   This research conducted with qualitative method in descriptive shape. Snowballing method has been used to identify informans. Interactive Model data analysist has been used on these research to analyst in depth interview with informans (representative of community leaders, religion leaders, teachers, active individuals and beneficiaries), these interview gave some identification on strengths, weaknesses, opportuinities and threats, of PT. AIC  in order to give some CSR on environment’s programme development recommendation especially to preserve water resources in Harjosari Village.